2017
DOI: 10.1038/srep43604
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-induced miRNA-155 inhibits self-renewal of neural stem cells via suppression of CCAAT/enhancer binding protein β (C/EBPβ) expression

Abstract: Intracerebral inflammation resulting from injury or disease is implicated in disruption of neural regeneration and may lead to irreversible neuronal dysfunction. Analysis of inflammation-related microRNA profiles in various tissues, including the brain, has identified miR-155 among the most prominent miRNAs linked to inflammation. Here, we hypothesize that miR-155 mediates inflammation-induced suppression of neural stem cell (NSC) self-renewal. Using primary mouse NSCs and human NSCs derived from induced pluri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 81 publications
0
22
0
Order By: Relevance
“…To determine the mechanism by which miR-155 activates myogenic differentiation, we focused on the role of C/ebpβ. Until now, it has been well demonstrated that C/ebpβ is a direct target of miR-155-5p both in mice and humans [ 18 , 20 ]. Meanwhile, there is some evidence that C/ebpβ is an essential molecule for maintaining the undifferentiated state of MuSCs [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the mechanism by which miR-155 activates myogenic differentiation, we focused on the role of C/ebpβ. Until now, it has been well demonstrated that C/ebpβ is a direct target of miR-155-5p both in mice and humans [ 18 , 20 ]. Meanwhile, there is some evidence that C/ebpβ is an essential molecule for maintaining the undifferentiated state of MuSCs [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro overexpression experiments clearly showed that miR-155 activated myogenic differentiation of C2C12 model cells. Regarding the function of miR-155 as a differentiation activator, we recently reported that miR-155 blocks neural stem cell self-renewal by suppressing the expression of transcription factors involved in stemness both in mouse and human cells [ 18 ]. On the other hand, Seok et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study demonstrated that overexpression of miR-155 significantly increased TNF-α, IL-18, IL-6 and IL-1β levels in keratinocyte-induced HaCaT cells, through the NLRP3 inflammasome. Obora et al (18) described that inflammation-induced miR-155 inhibits self-renewal of neural stem cells. However, it remains to be elucidated how miR-155 regulates NLRP3 in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…A vast majority of clinically diagnosed cases are in the intermediate and advanced stage due to the lack of early specific symptoms and tumor markers for early detection and diagnosis, which has led to the high mortality of gastric cancer (13). Therefore, searching for tumor markers for the early screening or diagnosis of gastric cancer, together with developing agents with high efficiency and low toxicity is of great importance (14). The discovery of miRNAs is a milestone in the field of molecular biology (3).…”
Section: Discussionmentioning
confidence: 99%